AMAKASU MARU NO. 1: AN ANALYSIS OF A REMOTELY OPERATED VEHICLE SURVEY ON A WWII JAPANESE REQUISITIONED SHIPWRECK IN THE PACIFIC - Yoxsimer, Andrea Yvonne (East Carolina University, 2022)
The Pacific Theatre of World War II left behind a plethora of archaeological sites, many of which are still being located. In 2016, the National Oceanographic and Atmospheric Administration (NOAA)'s Okeanos Explorer mission to Wake Island located one such site. Utilizing a remotely operated vehicle (ROV), the team believed they had located the remains of the Japanese warship Hayate, but markings on the side of the vessel indicated that this was instead the site of Amakasu Maru No. 1 (Cantelas and Wagner 2016). Sunk by the US submarine Triton on 24 December 1942, Amakasu Maru No. 1 was a requisitioned water tanker in the Imperial Japanese Navy (IJN) (Jentschura et al. 1970). Vessel requisition was a common practice within the IJN and while some of these sites have been archaeologically investigated, many have yet to be located. This research provides a detailed study of the Amakasu Maru No. 1 wreck site utilizing a site formation framework. A detailed literature review was also conducted to determine the amount of archaeological research already completed on IJN requisitioned vessels throughout the Pacific and their current levels of site preservation. A comprehensive catalog of this subject was produced which will be of assistance to future researchers interested in developing a study on similar vessels throughout the region. To make the subject material more accessible to the public, an ESRI Story Map was developed utilizing the cataloged information detailing the placement, as well as the extent of research, that has been conducted on each of these sites.
Keywords: Imperial Japanese Navy; site formation; requisitioned vessel; Japan--Kaigun--History--20th century; Japan--History, Naval--1868-1945; World War, 1939-1945--Japan; Underwater archaeology--Japan; Seizure of vessels and cargoes